COG 11.3 New Features - Heinrichs David; Lent Edward; Lee Chuck (EPJ Nuclear Sciences & Technologies)
COG is a high fidelity, multi-particle, Monte Carlo radiation transport code in development at LLNL since 1980 in support of multiple applications including nuclear criticality safety, radiation shielding, radiography, and subcritical multiplicity analysis. COG 11.3 is the latest version scheduled for public release in 2024 representing the culmination of ten years of development since previous releases. This paper describes the major new features available in COG 11.3 including: (a) updated nuclear data libraries; (b) updated activation data; (c) advanced LLNL Fission Reaction Event Yield Algorithm; (d) new time-tagged list-mode detector feature; (e) new spontaneous fission source feature; (f) new alpha and deuteron particle transport; (g) updated electron transport (implementing EGS5 with internal electron library generation using PEGS5); (h) three new estimators for the effective delayed neutron fraction; (i) new input pre-processor options for user-friendly generation of three-dimensional rectangular and triangular lattice geometries; (j) new parallel-processing capabilities for the inverse reactor period and CritDetVR features using MPI; (k) a new imaging detector feature; and (l) details of the modernized COG website at https://cog.llnl.gov. Like previously released versions, COG11.3 will be available to users through RSICC at ORNL, the Nuclear Energy Agency Data Bank at OECD, and by special arrangement through LLNL.